La nuit entre histoire et littérature - Alain Cabantous (Ateliers d'Anthropologie)
What role might literary works have played in the negative perception of the night and its criminalisation in modern times? Even if sources of this kind present the historian with methodological problems, the use of this documentation cannot be neglected when trying to understand the nocturnal, given that theatre, poetry and inexpensive books have spread and given root to a repellent and crime-generating representation of nocturnal time generally associated with violence of all kinds, with fear, and with death. But the comparative approach to night between France and England not only reveals different sensibilities, but also shows that night was an original creative wellspring that spread, among a broad Western European public, its terrifying models of night, conveyed no less by Elizabethan theatre than by tomb poetry or gothic novels.